Geochemical Characteristics of Metamorphic Rock-Hosted Gold Deposit At Onzon-Kanbani Area, Central Myanmar - Aung Tay Zar; I Wayan Warmada; Lucas Donny Setijadji; Koichiro Watanabe (Journal of Geoscience, Engineering, Environment, and Technology, 2017)
Gold and associated base metal mineralization of Onzon-Kabani area located in the western border of generally N-S trending Mogoke Metamorphic Belt where well-known Sagaing fault is served as a western boundary of this area. In this research area, many artisanal and small-scale gold mines were noted in last three decades. Gold mineralization is hosted in marble and gneiss unit of research area but most common in marble unit. Variety of igneous intrusions are also observed in research area. Mineralizations are observed as fissure filling veins as well as lesser amount of disseminated nature in marble unit. Mineralogically, gold are associated with other base metal such as pyrite, galena, sphalerite, chalcopyrite, marcasite and arsenopyrite. Hydrothermal alteration halos are developed in peripheral of hydrothermal conduits or mineralization veins from proximal to distal such as 1) silicic, 2) sericite-illite, and 3) propylitic alteration. Most of hydrothermal minerals from each altered zones showed that near neutral condition of pH (e.g. adularia, calcite, illite, sericite and chlorite). Alternatively, hydrothermal alteration zones that show with ore minerals such as native gold, electrum, sphalerite, galena, chalcopyrite, arsenopyrite and marcasite which mostly observed in silicic alteration zone. Typical boiling characters of vein textures and fluid inclusion petrography are observed in hydrothermal system of research area. Boiling, cooling and mixing are possiblily responsible for gold deposition in hydrothermal system. In this paper, authors are documented to clarify the type of mineralization based on hydrothermal alterations, ore and gangue mineral assemblages and fluid inclusion study. All of these data can describe and play an important role for both with respect to understanding deposit genesis and in mineral exploration.